The right to die: Its biomedical aspects - Teuku Jacob, Teuku Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
This article discussed the existence or non-existence of the right to die. Death has various facets, namely the biomedical, social, historical, moral and religious. Man has the right to live or not to be killed, but not the reciprocal right to die or to kill, although in borderline cases this is debatable. The right to die is executed by way of suicide and voluntary euthanasia.Suicide is committed due to hopelessness, shame or guilt feeling, terminal illness, loyalty to a dead person, and for political reasons. It can be performed by an individual, a pair (suicide pact), a family, a group or en masse. The medical profession should prevent all suicidal attempts and help the surviving victim, since it is its duty to prolong life and ameliorate suffering.Euthanasia is either positive or negative (not infrequently, and inaccurately, termed active or passive), voluntary or involuntary, direct or indirect, and by not implementing extraordinary or ordinary procedures in life saving. Reasons are put forward why euthanasia is condoned or condemned. The moral difference between the two forms of euthanasia are questioned by some serious ethicists. Conditions for negative euthanasia are presented if it is performed selectively, for which the demand is unfortunately real.Key Words: right to die-euthanasia-suicide-patient rights - bioethics